Evolution of Landing Systems in Land Society of Dnieper Ukraine in the Twenties of XX Century - Калініченко, Вячеслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The problems of farming systems in the pre-kholkhoz village of Naddnipryanshina in the 1920s are considered. Varieties of farming systems are investigated and their evolution in land communities is traced. It was revealed that the land communities had the potential to improve peasant agriculture and increase the volume of agricultural production.